2012
DOI: 10.1371/journal.pone.0037432
|View full text |Cite
|
Sign up to set email alerts
|

Full-Exon Pyrosequencing Screening of BRCA Germline Mutations in Mexican Women with Inherited Breast and Ovarian Cancer

Abstract: Hereditary breast cancer comprises 10% of all breast cancers. The most prevalent genes causing this pathology are BRCA1 and BRCA2 (breast cancer early onset 1 and 2), which also predispose to other cancers. Despite the outstanding relevance of genetic screening of BRCA deleterious variants in patients with a history of familial cancer, this practice is not common in Latin American public institutions. In this work we assessed mutations in the entire exonic and splice-site regions of BRCA in 39 patients with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 48 publications
4
35
2
7
Order By: Relevance
“…1820 The current study demonstrates a remarkably high prevalence of BRCA mutations among breast and ovarian cancer cases not selected for family history (15% and 28%, respectively) in Mexico, which is higher than expected compared to previous data obtained from a population-based breast cancer registry series in the U.S., where the BRCA1 prevalence was 3.5% among Hispanics (n=393) aged <65, and 8.9% for patients <35 years. 21 Only our recently published high-risk clinic-based population (n=746) study had a higher prevalence (25%).…”
Section: Discussioncontrasting
confidence: 63%
“…1820 The current study demonstrates a remarkably high prevalence of BRCA mutations among breast and ovarian cancer cases not selected for family history (15% and 28%, respectively) in Mexico, which is higher than expected compared to previous data obtained from a population-based breast cancer registry series in the U.S., where the BRCA1 prevalence was 3.5% among Hispanics (n=393) aged <65, and 8.9% for patients <35 years. 21 Only our recently published high-risk clinic-based population (n=746) study had a higher prevalence (25%).…”
Section: Discussioncontrasting
confidence: 63%
“…Even when comparing more comprehensive studies, in which the whole coding sequence and exon-intron boundaries of the BRCA genes were analyzed, significant heterogeneity exists in the mutation prevalence rates observed throughout Latin America. In Mexico, BRCA mutation prevalence varies from 10.2% in HBOC patients [28] to 21% (including large genomic rearrangements) in breast and ovarian cancer patients unselected for family history [20]. In Argentina, a prevalence of 28.3% was reported in series of breast or ovarian cancer patients selected for age at diagnosis and positive cancer family history [29], and a similar prevalence (24.5%) was found by Torres et al [30] in Colombian patients with breast and/or ovarian cancer and a family history of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have evaluated BRCA mutation in Latin American countries, and some of them have documented prevalence studies in high-risk population and in unselected invasive BC cases in Mexico (six total studies, 6.3-23.0% in high risk, 4.3% in unselected) [34][35][36], Brazil (eight studies, 3.4-22.5%, 2.3%) [37][38], Argentina (two studies, 16.2-58.3%, unknown) [33,39], Colombia (five studies, 14.3-24.5%, 1.2-4.5%) [40][41], Chile (two studies, 7.1-20.4%, unknown) [42], Costa Rica (one study, 4.5%, unknown) [43], Cuba (one study, 2.6%, unknown) [44], Peru (one study, 4.9%, unknown) [45], Uruguay (one study, 17%, unknown) [46], Venezuela (one study,17.2%, unknown) [47], Trinidad and Tobago (one study, unknown, 10.4%) [48] and The Bahamas (one study, 27.1%, unknown) [49]. Most Latin American studies identified a higher rate of BRCA1 than BRCA2 mutations [37], however studies from Costa Rica [43], Cuba [50], Puerto Rico [51] and Uruguay [46] reported the opposite finding.…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 99%